Relationship between social culture, industry 4.0, and organizational performance in the context of emerging economies - Iliana E. Aguilar-Rodríguez; César A. Bernal-Torres; Juan C. Aldana-Bernal; Andrés G. Acosta-Aguinaga; Carlos H. Artieda-Cajilema; Priscila Chalá (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: Was examined the relationship between social culture, Industry 4.0 technologies, and organizational performance in companies from emerging countries. Design/methodology/approach: Were chose medium and large companies from emerging Latin American economies. Colombia and Peru as the most advanced economies, and Ecuador for being in the first phase of growth. It was Data from 428 workers collected through online surveys. The data analysis was carried out using a Structural Equation Model. Findings: The results indicated a relationship between Industry 4.0 technologies and organizational performance and social culture and organizational performance. Furthermore, social culture does not mediate the relationship between Industry 4.0 technologies and organizational performance. Differences were also found among countries. Evidence is provided that Industry 4.0 technologies and social culture lead to better organizational performance. Practical implications: This study showed that, in the context of analysis, the level of maturity regarding the use of 4.0 technologies of medium and large companies is still incipient. Provides (1) information on cultural differences, mainly in the dimensions of Masculinity, Power Distance, and Individualism; and (2) guidelines on the use of Industry 4.0 technologies and their implication in Organizational Performance. Originality/value: The research results provide knowledge of the relationship between 4.0 technologies, social culture, and organizational performance in the context of emerging economies where the subject has been little investigated.
Keywords: 650; culture dimensions; emerging economies; Latin America; medium-sized and large businesses; national culture; organizational performance; digital transformation